Firm market power and the earnings distribution - Douglas A. Webber (Institute for the Study of Labor (IZA), 2013)
Using linked employer-employee data, I compute firm-level measures of the labor supply elasticity facing each private non-farm firm in the US. I provide the first direct evidence of the positive relationship between a firm's labor supply elasticity and the earnings of its workers. I also contrast the dynamic model method employed by this paper with the more traditional use of concentration ratios to measure a firm's labor market power. Finally, I construct a counterfactual earnings distribution which allows the effects of firm market power to vary across the earnings distribution.
Keywords: J42; J21; 330; monopsony